The evolution of shoulder injuries in junior handball players - Dorobăț Simona Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2024)
The prevalence of shoulder trauma in handball underscores the importance of medical rehabilitation for these injuries, making it a priority for researchers. This study aims to analyze and correlate data regarding the frequency of shoulder injuries, the age of injured athletes, the degree of disability, and the impact of the injury on their quality of life. We selected 40 athletes with instability injuries from 337 handball athletes, and they were distributed in two lots: LE= 20 athletes and the LC=20 athletes. We initially evaluated both groups using the DASH questionnaire, and the Burckhardt and Anderson quality of life questionnaire. The athletes in the LE group followed a rehabilitation plan structured into five phases, combining kinetic rehabilitation techniques with handball-specific exercises. Meanwhile, the athletes in the LC group followed a standard rehabilitation plan. We re-evaluated both groups using the same methods at the final program. The results emphasize that athletes in the LE group recorded significant improvements in both the DASH score and the quality of life score, indicating that the specialized rehabilitation plan had a positive effect on the handball players who followed it.